Research priority of the potential earthquake on the java island using decision making analysis - Lestari Wien; Widodo Amien; Syaifuddin Firman; Warnana Dwa Desa (E3S Web of Conferences, 2020)
Referring to the Indonesian earthquake source and hazard map published by the National Earthquake Center (Pusgen) in 2017, it was stated that there were 34 active faults on the island of Java and could potentially be a source of earthquakes with earthquake strength more than the 6.5 M scale. Each potential source of earthquake needs to be carried out detailed research on each fault that is declared active so as to reduce uncertainty in the seismic hazard analysis. Due to limited funding and human resources researching, it is necessary to make research priorities based on the level of urgency. By utilizing decision making analysis techniques, priority of research is carried out by considering several aspects, such as the magnitude of the earthquake that may occured possible economic impact factors, population density and the level of importance of a region on a national and international scale. From the modeling results, it is shown that faults that have the potential to become earthquake sources that are located near large cities are a top priority for detailed research such as the Lembang, Semarang and Surabaya Faults.